Answer: Option B
B. [tex]\frac{9}{26}[/tex]
Step-by-step explanation:
We have the following equations:
[tex]2x + \frac{4}{3}y = 1[/tex] (1)
[tex]y -\frac{9}{13}x=9[/tex] (2)
Let us call "a" the coefficient of the variable x in the first equation and call "b" the coefficient of the variable x in the second equation.
Then we must multiply the number "a" by a value z such that when adding [tex]az + b[/tex] the result is zero.[tex]a = 2[/tex]
[tex]b = -\frac{9}{13}[/tex]
So
[tex]2z-\frac{9}{13} = 0[/tex]
We solve the equation for z
[tex]2z=\frac{9}{13}[/tex]
[tex]z=\frac{9}{26}[/tex]
The first equation must be multiplied by a value of [tex]\frac{9}{26}[/tex]